2019
DOI: 10.31223/osf.io/t28zx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subduction history reveals Cretaceous slab superflux as a possible cause for the mid-Cretaceous plume pulse and superswell events

Abstract: Subduction is a fundamental mechanism of material exchange between the planetary interior and the surface. Despite its significance, our current understanding of fluctuating subducting plate area and slab volume flux has been limited to a range of proxy estimates. Here we present a new detailed quantification of subduction zone parameters from the Late Triassic to present day (230 – 0 Ma). We use a community plate motion model with evolving plate topologies to extract trench-normal convergence rates through ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…To limit the model parameter space and not introduce additional degrees of freedom in the absence of similarly rigorous observational constraints for both epochs, we again take arc and MOR lengths to remain unchanged through the Pangean and Rodinian cycles. We neglect, for example, new plate motion modeling constraints suggesting that an increase in MOR length contributed to a factor of 2 increase in the flux of material subducted at continental arcs from 180 to 130 Ma (East et al, ). We also ignore contributions of crustal carbonate to magmatism and to topography production and weathering since Pangea breakup (Lee et al, , ).…”
Section: Supercontinental Climate Control In An Evolving Mantle Thermmentioning
confidence: 99%
See 2 more Smart Citations
“…To limit the model parameter space and not introduce additional degrees of freedom in the absence of similarly rigorous observational constraints for both epochs, we again take arc and MOR lengths to remain unchanged through the Pangean and Rodinian cycles. We neglect, for example, new plate motion modeling constraints suggesting that an increase in MOR length contributed to a factor of 2 increase in the flux of material subducted at continental arcs from 180 to 130 Ma (East et al, ). We also ignore contributions of crustal carbonate to magmatism and to topography production and weathering since Pangea breakup (Lee et al, , ).…”
Section: Supercontinental Climate Control In An Evolving Mantle Thermmentioning
confidence: 99%
“…Figure 5 and Lenardic et al, 2011;Robin et al, 2007;Thayalan et al, 2006). Plate reconstructions and geological data suggest that subduction zones probably encircled Rodinia and to a lesser extent Pangea by the time these supercontinents were each formed (e.g., East et al, 2019;Evans, 2009;Lee et al, 2013;Le Pichon et al, 2019;Li et al, 2013;Müller et al, 2016). Depending on the continuity, geometry, and age of subducting slabs, such a planform can have varied consequences for the character and extent of mantle thermal mixing.…”
Section: The Mantle Response To the Assembly And Breakup Of Supercontmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, many hypotheses have been proposed to explain the extinction of dinosaurs 39 , and little is known about the drivers of a putative decline 3 , 10 , 11 , 28 , 31 , 40 . Identifying causal mechanisms for the demise of dinosaurs can be challenging because there are so many possibilities in the Cretaceous, including the continued breakup of the supercontinents Laurasia and Gondwana 41 , 42 , intense and prolonged volcanism 43 , climate change, fluctuations in sea levels 44 , 45 , and novel ecological interactions with rapidly expanding clades like flowering plants 46 49 and mammals 50 52 . Testing and teasing apart the effect of all these drivers on dinosaur diversification remain difficult, and, for instance, previous studies have found mixed support for the hypothesis that global dinosaur diversity is tied to sea-level fluctuations 18 , 40 , 53 , 54 .…”
Section: Introductionmentioning
confidence: 99%
“…Note the strong time-dependence, and that present-day heat loss from Earth's mantle represents an absolute minima for the 400-0 Ma time period, having been up to ∼15 TW higher in the past (Figure 1b). These variations are driven by changes to the age-area distribution of the seafloor (Figure 1c), which are caused by fluctuations in the rates of seafloor spreading and subduction during the supercontinent cycle (e.g., East et al, 2020;Karlsen et al, 2019a). This emphasizes the need for a long time-series (ideally spanning one complete supercontinent cycle) of heat flow to robustly infer long-term average values.…”
Section: Estimating Mantle Heat Loss Variationsmentioning
confidence: 99%